2010
DOI: 10.1371/journal.pone.0008610
|View full text |Cite
|
Sign up to set email alerts
|

Listeriolysin O Is Necessary and Sufficient to Induce Autophagy during Listeria monocytogenes Infection

Abstract: BackgroundRecent studies have suggested that autophagy is utilized by cells as a protective mechanism against Listeria monocytogenes infection.Methodology/Principal FindingsHowever we find autophagy has no measurable role in vacuolar escape and intracellular growth in primary cultured bone marrow derived macrophages (BMDMs) deficient for autophagy (atg5−/−). Nevertheless, we provide evidence that the pore forming activity of the cholesterol-dependent cytolysin listeriolysin O (LLO) can induce autophagy subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 58 publications
(103 reference statements)
5
79
0
Order By: Relevance
“…157 LLO was shown to be necessary and sufficient for SLAP formation, revealing a role for LLO in the vacuolar replication of L. monocytogenes, and suggesting that this bacterium is able to induce chronic infection of host macrophages. 157,158 Intracellular motility and cell-to-cell spread. The polarized bacterial surface protein ActA is one of the major virulence factors of L. monocytogenes.…”
Section: Monocytogenesmentioning
confidence: 99%
“…157 LLO was shown to be necessary and sufficient for SLAP formation, revealing a role for LLO in the vacuolar replication of L. monocytogenes, and suggesting that this bacterium is able to induce chronic infection of host macrophages. 157,158 Intracellular motility and cell-to-cell spread. The polarized bacterial surface protein ActA is one of the major virulence factors of L. monocytogenes.…”
Section: Monocytogenesmentioning
confidence: 99%
“…It has been known for some time that low concentrations of intracellular toxin affect host cell signalling in various ways, including activation of the p38 mitogen-activated protein kinase 8 , the c-Jun N-terminal pathways 9 and induction of pattern recognition receptors such as the NALP3 inflammasome 10 . In addition, LLO has been implicated in inducing autophagy 11 as well as in the suppression of reactive oxygen species produced by the NOX2 NADPH oxidase 12 . Over the past few years it has emerged that LLO activates diverse cellular processes including the dysregulation of post-translational modifications mediated by SUMOlyation 13 , induction of endoplasmic reticulum stress and reversible fragmentation of mitochondria 14 as well as regulatory epigenetic changes due to the post-translational modification of histone tails 15 .…”
mentioning
confidence: 99%
“…In addition, these authors confirmed that autophagy does not affect the fate of wild-type L. monocytogenes. 22 In other studies, Travassos et al used mouse embryonic fibroblasts (MEFs) to show that NOD1 and ATG16L are recruited to the plasma membrane at the site of L. monocytogenes entry, and that levels of LC3-positive bacteria in NOD1 -/-MEFs are significantly lower than in NOD +/+ MEFs. 23 Since L. monocytogenes deficient in LLO production are not decorated with LC3 in either NOD1 +/+ or NOD1 -/-MEFs, this suggests a functional link between the NOD1 and autophagy pathways, in which the plasma membrane ruptured by LLO becomes a target for autophagy.…”
mentioning
confidence: 99%